Sentinel lymph node mapping: current applications and future perspectives in thyroid carcinoma - Boschin, Isabella Merante; Bertazza, Loris; Scaroni, Carla; Mian, Caterina; Pelizzo, Maria Rosa (Frontiers in Medicine, 2023)
Sentinel lymph node (SLN) mapping is a standard, minimally-invasive diagnostic method in the surgical treatment of many solid tumors, as for example melanoma and breast cancer, for detecting the presence of regional nodal metastases. A negative SLN accurately indicates the absence of metastases in the other regional lymph nodes (LN), thus avoiding unnecessary lymph nodal dissection. Papillary thyroid carcinoma (PTC) is the most common type of thyroid carcinoma (TC) with cervical LN metastases at diagnosis in 20–90%, and nodal involvement correlates with local persistence/recurrence. The SLN in PTC is an intraoperative method for staging preoperative N0 patients and for detecting metastatic LNs “in and outside” the cervical LN central compartment; it represents an alternative method to prophylactic central neck node dissection. In this review we summarize different methods and results of the use of SLN in TC. The SLN identification techniques currently used include the selective vital-dye (VD) method, 99mTc-nanocolloid planar lymphoscintigraphy with intraoperative use of a hand-held gamma probe (LS), the combination LS + VD, and the combination LS and preoperative SPECT–CT (LS + SPECT/CT). The application of the SLN procedure in TC has been described in many studies, however, the techniques are heterogeneous, and the role of SLN in TC, with indications, results, advantages and limits, is still debated.